- The professional tendencies of a sample of adolescents in the city of Irbid in the light of some variables - a comparative study between deaf and normal adolescents - Musaada, Rafiee (Journal of Educational and Psychological Sciences, 2018)
The aim of the study was to identify the occupational tendencies of deaf and normal adolescents in the city of Irbid in the light of gender variables, adolescent nature, adolescence and monthly income. The study used the descriptive descriptive method and the questionnaire was a study tool. The sample consisted of 200 adolescents. And the statistical treatment of the SPSS program; the results showed that there were gender differences in professional orientation, with males having an average of 3.18 versus 3.07 for females and in realistic, analytical and commercial tendencies were higher among males with mean (3.04; 4.16; 2.91; (2.28; 4.13; 2.21) for males; and the results showed differences between (2.72; 4.03; 2.79) for females, and social, traditional and artistic tendencies were higher among females (2.48; 4.28; 2.75) Deaf teenagers and ordinary in professional tendencies, analytical, commercial and traditional tendencies were higher among ordinary adolescents, Jol social and artistic was higher among deaf adolescents, except for realistic tendencies there were no differences. The results also revealed differences in the professional tendencies of the deaf and normal adolescents due to adolescence in favor of middle and late adolescence. The results showed differences in the professional tendencies of deaf and normal adolescents due to the monthly income variable in favor of monthly income (more than 751 JD). In view of the findings, a number of useful recommendations were recommended in dealing with this segment.
Keywords: occupational orientation; gender differences; deaf adolescents; monthly income